Remuneration Factors Production of The Cultivation Brown Rice (Oryza Nivara) in Teluk Lombung Village Babirik District Hulu Sungai Utara Regency - Yudi Ferrianta; Rifiana Rifiana (TROPICAL WETLAND JOURNAL, 2019)
Geographically, Hulu Sungai Utara Regency is one of the regencies in South Kalimantan which is one of the regions producing brown rice with good results to develop. The land in Hulu Sungai Utara Regency is an average of swampland and rainfed, to plant brown rice only once a year. Brown rice is one type of rice that contains high nutrition. Based on the nutritional content, brown rice is very good for food-insecure areas, especially people who are malnourished. Farmers are less interested in planting brown rice although the selling price of red rice is higher than white rice and there is public awareness of the importance of the nutritional content of red rice for health so that the prospect of brown rice is very good to be cultivated. This research is raining to find out the costs, revenues, and profits of brown rice, to find out compensation for brown rice farming and to find out the problems faced in brown rice farming. The type of data used includes primary data and secondary data. The total sample of respondents was 11 farmers using the census method. The average land area used by brown rice farmers is 0.46 Ha. Based on the results of research on brown rice, it includes preparation of seedlings, land preparation, planting, maintenance, harvesting. The total costs incurred by farmers are Rp. 7,940,572, - per farm or Rp.17,303,649, - per ha. The total farmer income is IDR 14,784,000 per farm or IDR 32,139,130 ​​per ha. The total income of brown rice farmers is IDR 13,730,053 per farm or IDR 29,847,942 per ha. The benefits obtained by farmers are Rp.6,843,428, - per farm or Rp.14,835,481, - per ha. Repayment of farmers' capital is Rp.6,843,428, - per farm. Land compensation is Rp.6,843,428, - per farm. Retribution for labor in the family of brown rice farmers is IDR 6,799,348 per farm. The problem of brown rice farmers is that it is mostly an obstacle in regulating water, the difficulty of obtaining new land to cultivate brown rice, the difficulty of marketing the results of red rice to the community and the benefits of labor received by the red rice farmers smaller than the UMR of Hulu Sungai Regency North.